Challenges and opportunities in augmentative and alternative communication: Research and technology development to enhance communication and participation for individuals with complex communication needs. (2nd January 2019) - Light, Janice; McNaughton, David; Beukelman, David; Fager, Susan Koch; Fried-Oken, Melanie; Jakobs, Thomas; Jakobs, Erik
Abstract: The field of augmentative and alternative communication (AAC) has witnessed significant changes since its inception. AAC services are now considered for a much greater number of individuals with complex communication needs and there are many more AAC options available as communication supports, including a proliferation of technologies. The scope and options for communication within society have increased substantially to include a wide array of digital and social media. Individuals with complex communication needs have increased expectations for participation and engagement across a full range of environments—education, employment, family, healthcare, and community living. Despite these advances, there remain critical challenges that must be addressed. This paper discusses key advances in the AAC field, delineates challenges, and discusses future directions to address these challenges, specifically as they relate to research and development to enhance AAC interventions and technologies for individuals with complex communication needs and their families.